Stereotactic Body Radiotherapy as Primary Treatment for Elderly Patients with Medically Inoperable Head and Neck Cancer - Vargo, John A.; Ferris, Robert L.; Clump, David A.; Heron, Dwight E. (Frontiers in Oncology, 2014)
Purpose: With a growing elderly population, elderly patients with head-and-neck cancers represent an increasing challenge with limited prospective data to guide management. The complex interplay between advanced age, associated comorbidities, and conventional local therapies such as surgery and external beam radiotherapy ± chemotherapy, can significantly impact elderly patients’ quality-of-life (QOL). SBRT is a well-established curative strategy for medical-inoperable early-stage lung cancers even in elderly populations; however there is limited data examining SBRT as primary therapy in head-and-neck cancer. Material/Methods: Twelve patients with medically-inoperable head-and-neck cancer treated with SBRT ± cetuximab from 2002 through 2013 were retrospectively reviewed. SBRT consisted of primarily 44Gy in 5 fractions delivered on alternating days over 1-2 weeks. Concurrent cetuximab was administer at a dose of 400mg/m2 on day -7 followed by 250mg/m2 on day 0 and +7 in n=3 (25%). Patient reported quality-of-life (PRQoL) was prospectively recorded using the previously-validated University-of-Washington Quality-of-Life Revised (UW-QoL-R). Results: Median clinical follow-up was 6-months (range: 0.5 – 29 months). The 1-year actuarial local progression-free survival, distant progression-free survival, progression-free survival, and overall survival for definitively treated patients were 69%, 100%, 69% and 64%, respectively. One patient (8%) experienced acute grade 3 dysphagia and one patient (8%) experienced late grade 3 mucositis; there were no grade 4-5 toxicities. Prospective collection of patient report quality-of-life as assessed by UW-QoL-R was preserved across domains. Conclusion: SBRT shows encouraging survival and relatively low toxicity in elderly patients with unresectable head-and-neck cancer; which may provide an aggressive potentially curative local therapy while maintaining quality-of-life.